Differences in health care utilization by access policy among newly arrived refugees in Germany. (30th September 2020) - Wenner, J; Biddle, L; Bozorgmehr, K
Abstract: Introduction: In the first few months after refugees arrive in Germany, access to healthcare in most states is granted via health care vouchers (HcVs) that are issued by local authorities. After 15 to 18 months or formal recognition of refugee status, access is granted via electronic health cards (eHC) issued by statutory health insurance funds. We analyze whether these access policies (HcV vs. eHC) are associated with differences in needs-based utilization. Methods: We use data from a cross-sectional survey among newly arrived refugees and asylum seekers (n = 560; response rate 41.7%) in Germany's 3rd largest federal state to analyze differences in reported utilization of GP and specialist services in the last 4 weeks. We use logistic regression to calculate odds ratios (OR), adjusting for socio-demographic characteristics, health status, duration of stay and proximity of service providers. Results: Fewer refugees with HcVs reported using GP or specialist services in the last four weeks compared to those using regular eHCs (GP: 52.76% vs. 61.48%; SP: 38.97 vs. 45.09%). For specialist use, this difference persisted after adjustment, with eHC users having significantly higher odds of needs-based utilization (OR: 2.00; 95%-CI: 1.01-3.95). After adjustment, odds for GP use are also higher among persons with eHC, but less significant (OR: 1.37; 95%-CI: 0.67-2.82). Furthermore, the lack of a HcV was the second most reported reason among HcV users to refrain from utilization (17.09% for specialist and 15.51% for GP use). Conclusions: The access model is associated with differences in needs-based utilization for specialist (and partly for GP) use after controlling for important confounders. The lack of (timely) HcV provision constitutes a relevant access barrier. The results provide evidence that with equal needs, refugees with HcVs have more difficulties accessing services. Key messages: Access policies are associated with differences in healthcare utilization among newly arrived refugees in Germany. Early access to health cards and the statutory health insurance is likely to facilitate need-based utilization of health services for newly arrived refugees.